Processos de inclusão escolar de alunos público-alvo da educação especial nos cursos de ensino médio do IFES Campus Itapina e a formação continuada de professores - Corona, Maria da Penha Alves Ribeiro (2021)
The study aims to understand the training demands of teachers of professional and technological education at Ifes campus Itapina aiming at the inclusion of students targeting Special Education enrolled in the High School Courses of this teaching unit. It unfolds in the following specific objectives: a) to critically understand the educational policy of Ifes on the campus of Itapina and the Special Education policies present; b) ) create a listening network with the institution's teachers to understand the challenges and possibilities of including students targeting Special Education audiences, the demands pointed out by teachers to understand the teachers' continuing education needs; c) analyze the training requirements and search for themes that the professionals involved in the research consider relevant to compose a training proposal based on the inclusion processes of the target audience of Special Education students at Ifes Campus Itapina; d) constitute as an educational product of the dissertation a proposal for continuing education built from the needs pointed out by the teachers and which can be implemented by the teaching unit. It is based on the contributions of Freire, Nóvoa e Tardif e Lessard and researchers from Special Education to discuss the offer of Secondary Education, Special Education and teacher training, as well as researchers in the teaching modality. It is based on qualitative research and on the assumptions of the case study, having as procedures: a) request for authorization from the competent body and the subjects involved to carry out the study and the organization of the training process; b) documentary consultation: understanding of the history of the city of Colatina/ES, the educational policy present in it and the school researched in the interface with Special Education; c) application of questionnaires involving the Education professionals working at school to learn about the training processes experienced, the existing policies and the needs that the group considers important to explore in the moments of continuing education. It takes the period from April to December 2020 to produce the data, using the questionnaires and the field diary as recording instruments. It brings as participants of the research the direction of the teaching unit, the coordination of teaching and course, the pedagogues, the teachers of common education, the team of the Support Center for People with Specific Educational Needs (NAPNE). It presents as results: the enrollment of students targeting Special Education at Ifes / Itapina has demanded investment in teacher training; these investments strengthen the students 'and teachers' right to learn continuously to graduate; in continuing education policies, listening to teachers is a necessary action, as it allows the articulation of theory and practice; the inclusion of students targeting Special Education in Secondary Education is a challenge to be faced through the composition of several policies, among them, those aimed at teacher training, considering the social function of the school as everyone's time and Education professionals as subjects of knowledge and researchers of new other modes of mediation in an inclusive perspective.